The journal of media literacy education (National Association for Media Literacy Education, 2009)
"The Journal of Media Literacy Education is an online interdisciplinary journal that supports the development of research, scholarship and the pedagogy of media literacy education."--Http://www.amlainfo.org/publications/jmle.